2020
DOI: 10.47795/onns5189
|View full text |Cite
|
Sign up to set email alerts
|

Hallucinations in Parkinson’s disease: new insights into mechanisms and treatments

Abstract: Hallucinations are common in Parkinson’s disease and can be distressing to patients and their families. They are associated with higher rates of nursing home placement and with increased mortality. Their underlying mechanisms have been elusive, but recent advances in network imaging provides some intriguing insights into possible underlying drivers. Treatment is complicated by risk of worsening Parkinson’s motor symptoms and by higher rates of mortality with antipsychotics, but new therapeutic avenues are emer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 29 publications
0
24
0
Order By: Relevance
“…17,18 This has led to the speculation that the emergence of an aberrant top-to-down visual processing system dominating over the usual down-to-top system is perhaps key to the genesis of hallucinations in PD. [19][20][21] In this context, the possibility of a "cortical release" phenomenon has also been speculated in the past which could explain the abnormalities in the executive functions in PD-P group. 22 We observed significant impairment in the visuospatial function (visuospatial working memory, visual memory) in the PD-P group.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 This has led to the speculation that the emergence of an aberrant top-to-down visual processing system dominating over the usual down-to-top system is perhaps key to the genesis of hallucinations in PD. [19][20][21] In this context, the possibility of a "cortical release" phenomenon has also been speculated in the past which could explain the abnormalities in the executive functions in PD-P group. 22 We observed significant impairment in the visuospatial function (visuospatial working memory, visual memory) in the PD-P group.…”
Section: Discussionmentioning
confidence: 99%
“…In the 'fast'-progressing clusters, the presence of psychotic symptoms in the form of hallucinations or delusions was found as the strongest association. Indeed, hallucinations can already be observed in newly diagnosed patients [19] and experiencing such visual or auditory hallucinations was established to be one of the most notable risk factors for increased mortality [20] and earlier placement in care homes [21]. These findings could, on the one hand, be explained by the difficulties of living with psychosis but, on the other, also point towards a faster disease progression in general.…”
Section: Interpretation Of Significant Associations Between Variables...mentioning
confidence: 99%
“…Cholinesterase inhibitors may also ameliorate the gait disturbance and risk of falls in PD patients[ 103 ]. Furthermore, compared with PD dementia without psychosis, PD patients with concomitant dementia and psychosis were more likely to benefit from rivastigmine[ 104 , 105 ]. In a randomized, double-blind, placebo-controlled phase II single-center trial, donepezil showed a significant protective effect against the development of psychotic symptoms in PD patients with apolipoprotein E ε4 non-carriers, suggesting that ApoE ε4 allele status may contribute to the resistance of cholinesterase inhibitors[ 106 ].…”
Section: Treatment and Managementmentioning
confidence: 99%
“…In addition to improving cognitive performance, cholinesterase inhibitors may significantly alleviate hallucinations in patients with PD. Because the reported incidence of adverse effects of cholinesterase inhibitors is much lower than that of atypical antipsychotics, cholinesterase inhibitors may be an alternative treatment for improving “benign or minor” hallucinations, especially in PD dementia with psychosis[ 104 ].…”
Section: Treatment and Managementmentioning
confidence: 99%